2006 IEEE International Conference on Multimedia and Expo 2006
DOI: 10.1109/icme.2006.262862
|View full text |Cite
|
Sign up to set email alerts
|

Partial LDA vs Partial PCA

Abstract: Recently, 3D face recognition algorithms have outperformed 2D conventional approaches by adding depth data to the problem. However, independently of the nature (2D or 3D) of the approach, the majority of them required the same data format in the test stage than the data used for training the system. This issue represents the main drawback of 3D face research since 3D data should be acquired under highly controlled conditions and in most cases require the collaboration of the subject to be recognized. Thus, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The underlying idea is that global nonlinear data structures are locally linear and local structures can be linearly aligned. Rama and Tarres used the P2CA [24] and PLDA [25] to find the correspondence between the texture map and input image. Chai et al proposed a local linear regression (LLR) method [3], which extends the basic idea of linear object class to generate the virtual frontal view from a given non-frontal image.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying idea is that global nonlinear data structures are locally linear and local structures can be linearly aligned. Rama and Tarres used the P2CA [24] and PLDA [25] to find the correspondence between the texture map and input image. Chai et al proposed a local linear regression (LLR) method [3], which extends the basic idea of linear object class to generate the virtual frontal view from a given non-frontal image.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews of the related works can be found in [25] and [36]. In 2-D appearance-based face recognition methods, different dimension reduction techniques have been applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation